A history of Germany, 1918-2020 the divided nation - Fulbrook, Mary 1951- (Wiley Blackwell, 2021)
"I have amended and added to the text for this expanded fifth edition in a number of ways. In particular, the analysis of the Berlin Republic has been extended to the end of August 2020; the section on the Holocaust has been amended in light of an ever-expanding historiography that has significantly enhanced knowledge and understanding; and there have been minor revisions to content and analysis throughout the text, more in some chapters than others. As before, I have resisted the temptation to engage in radical alterations of style and argument that would have turned it into a substantially different book; but, aware that in some areas debates and approaches have moved on considerably, I have updated by light rewriting where relevant. A few additions and alterations have also been made to what remains a highly select bibliography at the end; this is not intended to be comprehensive, but merely to provide some starting points and suggestions for readers wishing to explore particular periods and topics in greater depth"--
Edition history: Fontana Ltd. (1e, 191), Blackwell Publishing Ltd. (2e, 2002), Mary Fulbrook (3e, 2009), John Wiley & sons, Lt. (4e, 2015)
Keywords: Geschichte 1918-2020; Deutschland; Germany / Politics and government / 20th century; Germany / Politics and government / 21st century; Politics and government; Germany; 1900-2099